PROSPECTS OF QUANTUM TECHNOLOGIES IMPLEMENTATION IN SECURITY OF E-BANKING SYSTEMS IN UKRAINE - Гнатюк, С. О.; Кінзерявий, В. М.; Приставко, С. В.; Дідич, Е. В. (Science-based technologies, 2009)
This article describes the analysis of current situation with information security in e-banking systems. Here are considered the most common security problems which may arise. And is shown how quantum technologies can solve such security problems of e-banking systems. Also here are described prospects of implementation quan-tum technologies in e-banking systems in Ukraine to enhance information security.